The primary care value chain of the supplementary system: an analysis of a private health plan (Research, Society and Development, 2022)
This paper aims to analyze the supply of primary health care (PHC) services in the supplementary health sector. The method employed was the application and elaboration of the Porter value chain (VC), based on a case study in a private health plan from the southern region of Brazil. It was possible to show that PHC services started to prioritize the Brazilian supplementary health, including regulation and incentive mechanisms by the National Supplementary Health Agency (ANS), due to its cost reduction potential. However, for the incorporation of PHC in the sector to occur sustainably, there is a need for an intense cultural change due to the solid medical tradition, which emphasizes the hospital model. More specifically, the main results were: i) PHC can add value to cooperative services, provided that investments are made in this technology; ii) the VC proved to be an adequate instrument to analyze the supply of PHC in supplementary health and could be used to outline strategies for operators to build their competitive advantage; and, iii) for the PHC plan analyzed, the generic strategy to be pursued would be to focus on differentiation.